Would Malaysian young parents get their children vaccinated? Extending the theory of planned behavior to the context of social media influence effectiveness - Noor Amira Syazwani, Abd Rahman; Nur Hazirah, Hamdan; Mohd Rozaimy, Ridzuan; Ju, Soon Yew; Jamal Rizal, Razali (Social Institute of Malaysia (ISM), 2023)
Parent approval of routine childhood vaccination is essential to sustaining children's health because high vaccination coverage rates lower vaccine-preventable diseases. Children are more susceptible to contagious diseases than adults; thus, delaying or refusing vaccination puts them at risk for serious health problems. Nevertheless, the choices made by parents regarding their children's vaccination are complex and multifaceted. Many Malaysian parents are worried about vaccines due to false information from sources in the media and the internet. The media spreads these myths, which has a direct impact on parental intentions. This study explored factors associated with young parents' intention to vaccinate their children. This study employs the theory of planned behaviour (TPB), in which intentions result from attitudes, subjective norms, perceived behavioural control and added social media. A cross-sectional survey was distributed to 210 Malaysian parents between 18 and 40 years old. However, only 202 questionnaires were usable for data analysis. The data was analysed using SMART-PLS 4.0 by applying a structural equation modelling approach. Results reveal that attitude, subjective norms, and social media significantly and positively influenced the children's vaccination intention.